2012
DOI: 10.7745/kjssf.2012.45.6.1108
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Application Effects of Fertilizers and Amendments on Changes of Soil Organic Carbon in Paddy Soil

Abstract: The changes of soil organic carbon (SOC) content in paddy soils (sandy loam) were assessed from data of the 59 years fertilization plots in which the continuous rice cropping experiment started in 1954. The treatments were no fertilization(no fert.), NPK fertilization (N, NPK), NPK plus rice straw compost (NPK+C), and NPK plus rice straw compost, silicate fertilizer and lime (NPK+CLS). After 41 years, SOC content in NPK+C and NPK+CLS treatment in surface soils (0∼15 cm) reached at the highest, followed by main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
1
0
0
1
Order By: Relevance
“…Our study concluded that an increase in the rate of crop residue, or application of FY-manure, especially in conjunction with the NT system, greatly increases the SOC stock through addition of SOM in the soil, and improves the capacity of soil to more sequester SOC. This finding is consistent with further studies ( Li et al., 1994 ; Qiu et al., 2009 ; Kim et al., 2012 ; Lehtinen et al., 2014 ; Zhang et al., 2018 ; Ku et al., 2019 ), which revealed that application of organic fertilizer and increasing crop residue rate lead to significant enhancement of SOC stock. Similarly, Zhang et al.…”
Section: Resultssupporting
confidence: 92%
“…Our study concluded that an increase in the rate of crop residue, or application of FY-manure, especially in conjunction with the NT system, greatly increases the SOC stock through addition of SOM in the soil, and improves the capacity of soil to more sequester SOC. This finding is consistent with further studies ( Li et al., 1994 ; Qiu et al., 2009 ; Kim et al., 2012 ; Lehtinen et al., 2014 ; Zhang et al., 2018 ; Ku et al., 2019 ), which revealed that application of organic fertilizer and increasing crop residue rate lead to significant enhancement of SOC stock. Similarly, Zhang et al.…”
Section: Resultssupporting
confidence: 92%
“…국내에서는 논토양에서 장기간에 걸쳐 동일비료를 장기간 연용하였을 때 벼의 수량과 토양의 화학성 변화에 대한 보고들이 있으나 (Yeon et al, 2007;Yang et al, 2010;Kim et al, 2012;Kim et al, 2017), 밭토양에 대해서는 이러 한 결과가 미흡한 실정이다. 고추의 경작면적은 2014년을 기준으로 36,120 ha로 노지 채소의 20%를 차지하고 있으 며 (www.kosis.kr), 김치를 만드는데 꼭 필요한 조미채소로 식생활에 없어서는 안 되는 중요한 작물이다 (Lim et al, 2008).…”
Section: Introductionunclassified
“…이러한 원인 중의 하나로 지 속적으로 볏짚환원과 사료작물인 이탈리안라이그라스 재배 지점이 증가한 것이 가장 큰 요인으로 보인다 (Fig.2). 이 는 유기물과 전용적밀도가 부의 상관관계가 있다고 보고된 결과(Ahn et al, 2010)와 장기연용 논 토양에서 볏짚퇴비 시용구의 심토 유기탄소 함량이 2배 정도 높아졌다는 결과와 같은 경향을 보였다(Kim et al, 2012).…”
unclassified